Chemical fertilizer reduction combined with organic fertilizer affects the soil microbial community and diversity and yield of cotton - Shi, YingWu; Niu, XinXiang; Chen, BaoZhu; Pu, ShengHai; Ma, HongHong; Li, Pan; Feng, GuangPing; Ma, XingWang (Frontiers in Microbiology, 2023)
The soil microbial community plays an important role in modulating cotton soil fertility. However, the effects of chemical fertilizer combined with organic fertilizer on soil chemical properties, microbial community structure, and crop yield and quality in arid areas are still unclear. This study aimed to explore the effects of different organic fertilizers on soil microbial community structure and diversity and cotton growth and yield. High-throughput sequencing was used to study the soil bacteria and fungi in different growth stages of cotton. The field fertilization experiment had five treatments.The results indicated that the treatments of chemical fertilizer reduction combined with organic fertilizer significantly increased soil available nitrogen and phosphorus in cotton field. There were significant differences in the abundance of the bacterial and fungal communities in the dominant phyla among the treatments. At the phyla level, there were not significantly different in the diversity of bacteria and fungi among treatments. There were significant differences in the composition and diversity of bacterial and fungal communities during the entire cotton growth period (p= 0.001).The rhizosphere bacterial and fungal community structure was significantly affected by soil TK, NH4 + , AK, TP, AN, and NO3 -. The different fertilization treatments strongly influenced the modular structure of the soil bacterial and fungal community cooccurrence network. A reduction in chemical fertilizer combined with organic fertilizer significantly improved cotton stem diameter and seed yield, and the effect of the biological organic fertilizer on plant growth and yield formation was greater than that of ordinary organic fertilizer.